2008
DOI: 10.1111/j.1540-8175.2008.00751.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tissue Doppler Imaging in the Noninvasive Detection of Chronic Rejection after Heterotopic Cardiac Transplantation in Rats

Abstract: TDI of the transplanted heart in rats is feasible, reproducible, and more sensitive than palpation for the detection of chronic rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In a study published in 2009, tissue Doppler imaging was able to show for the first time a correlation between systolic radial strain rate in the anterior wall and rejection grade but no correlation with ejection fraction during chronic rejection in a heterotopic rat cardiac transplant model although ejection fraction was clearly decreased at all grades of histological rejection 23. This was followed by another study using a different technique of magnetic resonance strain imaging that showed decreased circumferential strain despite normal ejection fraction in a rat heart-lung transplant model 24.…”
Section: Discussionmentioning
confidence: 97%
“…In a study published in 2009, tissue Doppler imaging was able to show for the first time a correlation between systolic radial strain rate in the anterior wall and rejection grade but no correlation with ejection fraction during chronic rejection in a heterotopic rat cardiac transplant model although ejection fraction was clearly decreased at all grades of histological rejection 23. This was followed by another study using a different technique of magnetic resonance strain imaging that showed decreased circumferential strain despite normal ejection fraction in a rat heart-lung transplant model 24.…”
Section: Discussionmentioning
confidence: 97%
“…We can conclude that the role of assessment of filling pressure in a transplanted heart is limited regarding detect rejection. There are some reports on the use of myocardial deformation imaging that are promising but still echocardiography cannot replace endomyocardial biopsies for surveillance of rejection . Second, the easily obtained echocardiographic assessment of filling pressures could help the clinician to adjust diuretics that are commonly used in HTx recipients, especially in the first year post transplant until the heart fully recovers.…”
Section: Discussionmentioning
confidence: 99%
“…Transthoracic Echo was done on all animals at baseline, 3 days, 2 weeks, 4 weeks, and 16 weeks post‐surgery as described previously (Jassal et al, 2009 ; Kaur et al, 2006 ). The parameters measured included: heart rate (HR), left ventricular end diastolic diameter (LVEDd), LV end systolic diameter (LVEDs), and LV ejection fraction (LVEF).…”
Section: Methodsmentioning
confidence: 99%